"Nowhere does it say that in the Bible": Tensions between Legal and Symbolic Meanings of Marriage for Lesbian Women in South Africa. Issue 1 (30th December 2014) - Scott, Jessica
Abstract : For lesbian women who marry in South Africa, religion is both a source of great opposition to their relationships and a tool that they can use to negotiate their belonging with family and friends, after deciding to exercise their citizenship through marriage. This article draws from qualitative research conducted in South Africa to explore the relationship between sexuality and religion in the context of legal same-sex marriage. Though religion has been previously implicated in the maintenance of oppressive regimes, such as colonialism and apartheid, it has also been one of the primary voices against such injustices. The article concludes by suggesting that lesbian women use their own understandings of religion and sexuality to actively participate in the formation of new opportunities for social, legal, and spiritual citizenship.